A novel tuned inerter eddy current damper: modeling, optimization, and evaluation. (15th June 2023) - Li, Yafeng; Tan, Ping; Li, Shouying; He, Hui
Highlights: A novel tuned inerter eddy current damper (TIECD) using a rack and gear mechanism is proposed. The TIECD design procedure for seismic control of primary structures is established based on the effective damping ratio enhancement effect. A closed-form solution for TIECD optimal design is presented using stochastic linearization techniques with force-based and energy-based equivalence criteria. The advantages of TIECD over tuned viscous mass damper (TVMD) are owing to the damping force limiting characteristics and small deformation. Abstract: This study proposes a novel tuned inerter eddy current damper using a rack and gear mechanism (TIECD), in which the configuration and mechanical model are introduced in detail. The TIECD design procedure for the seismic control of primary structures is established based on the effective damping ratio enhancement (EDRE) effect. A closed-form solution for TIECD optimal design under white noise excitation is presented using stochastic linearization techniques (SLT) with force-based and energy-based equivalence criteria. The control performance of the TIECD obtained by the closed-form solution, including the EDRE effect and effective damping ratio, is in good agreement with the numerical results obtained from the Monte Carlo simulation when a suitable TIECD critical velocity is selected; a large critical velocity is conducive to improving the accuracy of the closed-form solution. Note that the effect of a low structural damping level on the optimal design of TIECD can be ignored, which is beneficial in practical engineering applications because structural damping cannot be precisely known in most cases. Furthermore, several numerical studies have been conducted to investigate the availability of TIECD under real seismic excitations. The results indicate that the effectiveness of TIECD in mitigating the seismic response of primary structures is approximately the same as that of a tuned viscous mass damper (TVMD) and much greater than that of the viscous and eddy current dampers with the same damping parameters. It can be considered that the maximum damping force and maximum deformation of TIECD and TVMD are the key design factors for short-period and long-period structures, respectively, and the advantages of TIECD over TVMD are owing to the damping force limiting characteristics and small deformation.